Model pendampingan pengelolaan dan penguatan branding desa wisata menuju kemandirian ekonomi masyarakat - Djarot Heru Santosa; Hendrokumoro Hendrokumoro; Moh Masrukhi (Riau Journal of Empowerment, 2022)
The Community Service Program (PkM) was carried out by a team from the Department of Language and Literature, FIB-UGM in Ponjong Village, Ponjong District, Gunung Kidul Regency, Yogyakarta Special Region. In its implementation, the team synergizes with the Regional Government of Gunung Kidul Regency in a sustainable manner (2020-2022). First year 2020, it began with mapping the potential of the area and pre-conditions of PkM by the team together with Community Student Service (KKN) activities. In 2021, the preparation of the activities agenda, socialization, assistance in Community Organization Management (MOM), trainings and community empowerment. In the last year 2022, strengthening, branding tourist attractions in Ponjong Village, publication programs through social media, monitoring and evaluating the sustainability of the program. The result is the understanding of the people of Ponjong Village towards the current situation (pandemic period, pre-normal, and normal) and the formation of a strong and independent institution for tourism awareness groups and local/village economic drivers in utilizing the potential of the "Water Byur" tourist attraction in Ponjong Village.